Влияние внешнего периодического воздействия на автоколебания несимметричных однодисковых роторов в подшипниках скольжения произвольной длин - Аврамов, К.В.; Борисюк, А.В. (Проблемы машиностроения, 2013)
Предложена нелинейная математическая модель, описывающая взаимодействие вынужденных колебаний и автоколебаний в однодисковых упругих роторах. Для определения сил масляного слоя подшипников скольжения произвольной длины используется конечноэлементная процедура. Результаты расчета периодических колебаний представляются на амплитудно-частотной характеристике. Исследованы почти периодические колебания ротора. Запропонована нелінійна математичка модель, що описує взаємодію вимушених коливань та автоколивань в однодискових гнучких роторах. Для визначення сил масляного шару підшипників ковзання довільної довжини використовується скінченноелементна процедура. Результати розрахунку періодичних коливань подані на амплітудно-частотній характеристиці. Досліджені майже періодичні коливання ротора. Nonlinear dynamics of one disk elastic rotor is treated. The shaft is attached in two arbitrary length journal bearings. Unbalance between disk center mass and point of disk attaching to the shaft takes place. The forced vibrations occur due to this unbalance, which always present in a disk. The self-sustained vibrations caused by interaction between fluid film and journal. Nonlinear mathematical model of interaction of forced vibrations and self-sustained vibrations in onedisk elastic rotors is treated. Finite element procedure is used to analyze forces of oil film. The forces of the journal bearings are calculated if form of power series with respect to the generalized displacements and the velocities of the journal. The results of nonlinear analysis of rotor dynamics are presented on frequency responses. The region of almost periodic vibrations is calculated. Both periodic monoharmonic vibrations and the almost periodic motions are observed in the above-mentioned frequency range.